The role of teacher empathy and immediacy in Chinese EFL students’ affective learning outcomes: unveiling the associations - Wang, Nana; Kang, Jiafang (Frontiers in Psychology, 2023)
Introduction: The positive influences of teacher-student interpersonal communication skills on second language (L2) students have been considerably endorsed in the literature. However, the contribution of teacher empathy and immediacy behaviors, as realizations of such skills, to students’ affective learning outcomes is unaddressed in L2 research. Methods: To fill this gap, three scales were distributed among a sample of 350 Chinese EFL students to see if teachers’ empathy and immediacy correlate with and predict students’ affective learning outcomes. Results: The results of correlation analysis revealed strong and positive relationships among teacher empathy, teacher immediacy, and learners’ affective learning outcomes. Moreover, the results of multiple regression indicated that Chinese EFL teachers’ empathy and immediacy could predict about 65% and 60% of changes in the learners’ affective learning outcomes, respectively. Discussion: Implications of the study for EFL teachers’ interpersonal communication skills development and emotional literacy are discussed. Future research trends are also presented at the end of the article.